Do island plant populations really have lower genetic variation than mainland populations? Effects of selection and distribution range on genetic diversity estimates - C. García‐Verdugo; M. Sajeva; T. La Mantia; C. Harrouni; F. Msanda; J. Caujapé‐Castells (Molecular Ecology, 2015)
Ecological and evolutionary studies largely assume that island populations display low levels of neutral genetic variation. However, this notion has only been formally tested in a few cases involving plant taxa, and the confounding effect of selection on genetic diversity ( GD ) estimates based on putatively neutral markers has typically been overlooked. Here, we generated nuclear microsatellite and plastid DNA sequence data in Periploca laevigata , a plant taxon with an island–mainland distribution area, to (i) investigate whether selection affects GD estimates of populations across contrasting habitats; and (ii) test the long‐standing idea that island populations have lower GD than their mainland counterparts. Plastid data showed that colonization of the Canary Islands promoted strong lineage divergence within P. laevigata , which was accompanied by selective sweeps at several nuclear microsatellite loci. Inclusion of loci affected by strong divergent selection produced a significant downward bias in the GD estimates of the mainland lineage, but such underestimates were substantial (>14%) only when more than one loci under selection were included in the computations. When loci affected by selection were removed, we did not find evidence that insular Periploca populations have less GD than their mainland counterparts. The analysis of data obtained from a comprehensive literature survey reinforced this result, as overall comparisons of GD estimates between island and mainland populations were not significant across plant taxa ( N = 66), with the only exception of island endemics with narrow distributions. This study suggests that identification and removal of markers potentially affected by selection should be routinely implemented in estimates of GD , particularly if different lineages are compared. Furthermore, it provides compelling evidence that the expectation of low GD cannot be generalized to island plant populations.